Reproducing normative femininity: Women's evaluations of their birth experiences analysed by means of word frequency and thematic analysis - Agneta Westergren; Kerstin Edin; Monica Christianson (BMC, 2021)
Abstract Background Given the significance of the birth experience on women's and babies' well-being, assessing and understanding maternal satisfaction is important for providing optimal care. While previous research has thoroughly reviewed women's levels of satisfaction with the childbirth experience from a multitude of different angles, there is a dearth of papers that use a gender lens in this area. The aim of this study is to explore through a gender perspective the circumstances attributed to both women's assessment of a positive birth experience and those which contribute to a lack of satisfaction with their birth experience. Methods Through the use of a local birth evaluation form at a Swedish labour ward, 190 women gave written evaluations of their birth experiences. The evaluations were divided into groups of positive, ambiguous, and negative evaluations. By means of a latent and constructionist thematic analysis based on word count, women's evaluations are discussed as reflections of the underlying sociocultural ideas, assumptions, and ideologies that shape women's realities. Results Three themes were identified: Grateful women and nurturing midwives doing gender together demonstrates how a gender-normative behaviour may influence a positive birth experience when based on a reciprocal relationship. Managing ambiguous feelings by sympathising with the midwife shows how women's internalised sense of gender can make women belittle their negative experiences and refrain from delivering criticism. The midwifery model of relational care impeded by the labour care organisation describes how the care women receive during labour and birth is regulated by an organisation not always adapted to the benefit of birthing women. Conclusions Most women were very satisfied, predominantly with emotional support they received from the midwives. The latent constructionist thematic analysis also elicited women's mixed feelings towards the birth experience, with the majority of negative experiences directed towards the labour care organisation. Recognising the impact of institutional and medical discourses on childbirth, women's birth evaluations demonstrate the benefits and challenges of gender-normative behaviour, where women's internalised sense of gender was found to affect their experiences. A gender perspective may provide a useful tool in unveiling gender-normative complexities surrounding the childbirth experience.